Inhibitory effects of propolis and essential oils on oral bacteria - Zoran Tambur; Biljana Miljković-Selimović; Dolores Opačić; Branislava Vuković; Adam Malešević; Luka Ivančajić; Ema Aleksić (Journal of Infection in Developing Countries)
Introduction: Propolis is a natural composite balsam. In the past decade, propolis has been extensively investigated as an adjuvant for the treatment of periodontitis. This study aimed to investigate antimicrobial activities of propolis solutions and plant essential oils against some oral cariogenic (Streptococcus mutans, Streptococcus mitis, Streptococcus sanguis, Lactobacillus acidophilus) and periodontopathic bacteria (Actinomyces odontolyticus, Eikenella corrodens, Fusobacterium nucleatum).